2022
DOI: 10.1097/gox.0000000000004426
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Improves Patient Experience and Anxiety During In-office Carpal Tunnel Release

Abstract: Background: This study examined how wide- awake local anesthesia no tourniquet (WALANT) surgery in the office versus the standard operating room (OR) impacts patient experience, and the effect wide awake virtual reality (WAVR) has in conjunction with WALANT on patient experience. Methods: This is a patient-reported outcome study of patients undergoing carpal tunnel release by a single surgeon between August 2017 and March 2021. Patients were classified by location; traditional OR versus WALANT in-office. In-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Potential concerns regarding transferring procedures from the operating room to the office include the risk of higher complication rates and poorer outcomes. However, current evidence suggests that these concerns may be unfounded [4][5][6][7]. Given the efforts to improve value in health care, further investigation is warranted to understand the association between operative settings and patient outcomes with CTR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential concerns regarding transferring procedures from the operating room to the office include the risk of higher complication rates and poorer outcomes. However, current evidence suggests that these concerns may be unfounded [4][5][6][7]. Given the efforts to improve value in health care, further investigation is warranted to understand the association between operative settings and patient outcomes with CTR.…”
Section: Resultsmentioning
confidence: 99%
“…While CTR procedures have been historically performed in a hospital-based operating room or ambulatory surgery center, advances in surgical techniques and anesthesia have allowed surgeons to perform the procedures in different operative settings. Because the operative setting is the primary cost driver of CTR [3], there has been recent interest in performing CTR in an office-based setting using local anesthesia, which may contribute to lower cost, faster patient recovery, greater patient satisfaction, and similar low complication rates [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] In healthcare, virtual reality (VR) platforms have been an effective strategy to reduce anxiety and pain via distraction during a variety of procedures including blood draws and intravenous (IV) catheter placement. [15][16][17][18][19][20][21][22][23] Pediatric patients who used immersive VR during peripheral IV catheter (PIVC) placement had significantly lower post-PIVC pain scores and post-PIVC anxiety scores compared to patients in the standard care group. 21 Distraction strategies in blood donors have helped to reduce anxiety and reaction symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that donation‐related fear and anxiety are a major deterrent for blood donation, cause attrition, and increase the likelihood of needle pain and vasovagal reactions 6–14 . In healthcare, virtual reality (VR) platforms have been an effective strategy to reduce anxiety and pain via distraction during a variety of procedures including blood draws and intravenous (IV) catheter placement 15–23 . Pediatric patients who used immersive VR during peripheral IV catheter (PIVC) placement had significantly lower post‐PIVC pain scores and post‐PIVC anxiety scores compared to patients in the standard care group 21 …”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has suggested a benefit of the use of VR during wide-awake hand surgery in reducing patient anxiety and improving patients’ experience. 14 , 15 , 16 However, further work is indicated to better understand this technology in different patient populations and settings as well as understand its impact on providers and clinical workflow. This study sought to assess whether immersive VR could decrease patient anxiety in veterans and what impact it had on both patients’ and providers’ experience during wide-awake, local-only hand surgery in a minor procedure room at a VAHCS hospital.…”
mentioning
confidence: 99%